2018
DOI: 10.2147/opth.s170698
|View full text |Cite
|
Sign up to set email alerts
|

Six-month results of intravitreal ranibizumab for macular edema after branch retinal vein occlusion in a single-center prospective study: visual outcomes and microaneurysm formation

Abstract: PurposeThe aim of this study is to report the 6-month results after one intravitreal ranibizumab (IVR) injection followed by pro re nata dosing for macular edema (ME) after branch retinal vein occlusion.Patients and methodsThe inclusion criteria included a minimal patient age of 18 years, 20 letters or more best-corrected visual acuity (BCVA) (Early Treatment Diabetic Retinopathy Study [ETDRS] score, 77 letters or less), and central retinal thickness (CRT) of 250 microns or more. The primary outcome measure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The mean number of injections and clinic visits was 4.26 (0.71) and 6.71 (1.41), respectively. The BCVA and CST values were consistent with those in previous reports [ 7 , 8 , 10 , 11 , 18 , 19 ], and the mean number of injections was similar to that of the one injection plus PRN regimen [ 10 , 11 ]. The mean number of clinic visits was similar to that in the TAE regimen [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean number of injections and clinic visits was 4.26 (0.71) and 6.71 (1.41), respectively. The BCVA and CST values were consistent with those in previous reports [ 7 , 8 , 10 , 11 , 18 , 19 ], and the mean number of injections was similar to that of the one injection plus PRN regimen [ 10 , 11 ]. The mean number of clinic visits was similar to that in the TAE regimen [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The mean number of clinic visits was similar to that in the TAE regimen [ 18 , 19 ]. Many previous studies investigated PRN and TAE regimens for BRVO [ 7 , 8 , 10 , 11 , 18 , 19 , 22 ], but this mTAE regimen is the first to combine the best features of PRN and TAE regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prompt administration (within 3 months after disease onset) of anti-VEGF agents was more effective than delayed administration (over 3 months after disease onset) [44], which supports the association between excessive VEGF expression and microaneurysm formation. Moreover, we reported the same effect in a prospective study with IV injection of ranibizumab in eyes with BRVO [109]. Furthermore, microaneurysms are seen frequently at the edge of the NPAs, which also indicates the association of VEGF with microaneurysm formation, because VEGF proteins are produced from the ischemic area.…”
Section: Microaneurysm and Macroaneurysmsupporting
confidence: 66%
“…One hypothesis to explain SSPiM are that these are particles remaining after resolution of a retinal hemorrhage plus fluid leakage from the broken BRB following venous obstruction. Another hypothesis is that SSPiM are related to microaneurysms because microaneurysms in BRVO are related to chronic disease and are known to be factors for ME relapse 2 , 21 , 22 . Microaneurysms in BRVO can occur at the junction of the nonperfused and perfused retina 23 , and one study suggested that microaneurysms are a secondary change caused by local hypoxia and increased VEGF concentration 9 .…”
Section: Discussionmentioning
confidence: 99%